2009
DOI: 10.1111/j.1471-0374.2009.00258.x
|View full text |Cite
|
Sign up to set email alerts
|

Mobile phones, communities and social networks among foreign workers in Singapore

Abstract: Transnational mobility affects both high-status and low-income workers, disrupting traditional assumptions of the boundedness of communities. There is a need to reconfigure our most basic theoretical and analytical constructs. In this article I engage in this task by illustrating a complex set of distinctions (as well as connections) between 'communities' as ideationally constituted through cultural practices and 'social networks' constituted through interaction and exchange. I have grounded the analysis ethno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
52
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(59 citation statements)
references
References 28 publications
(20 reference statements)
5
52
0
2
Order By: Relevance
“…Furthermore, my interviews and observations were often punctuated by incoming phone calls from home. The everyday banality that the mobile phone represents for hostel residents and their relatives remaining behind has also been documented by other authors in different migration contexts (such as Tazanu 2012; Thompson 2009). …”
Section: Dialling To Dembancané: the All-conquering Mobile Phonesupporting
confidence: 60%
See 1 more Smart Citation
“…Furthermore, my interviews and observations were often punctuated by incoming phone calls from home. The everyday banality that the mobile phone represents for hostel residents and their relatives remaining behind has also been documented by other authors in different migration contexts (such as Tazanu 2012; Thompson 2009). …”
Section: Dialling To Dembancané: the All-conquering Mobile Phonesupporting
confidence: 60%
“…As with household budgets, fixed and mobile phone technologies can be harnessed to coordinate and manage household activities (Hamel 2009;Thompson 2009;Wilding 2006), potentially giving migrants more influence over family members previously out of reach. Critically for this discussion, researchers have also found that emigrants can use such technology to better manage the expectations of their loved ones back home.…”
Section: Ict and Return Preparedness: Mobilizing Influence And Managimentioning
confidence: 99%
“…52 As John Urry suggests here, citizens' differential access to a range of mobility Mills / Thai Mobilities 107 50. See Knodel and Saengtienchai 2007;Knodel et al 2010;and Thompson 2009 for some initial quantitative and qualitative research on this topic. 51.…”
Section: Resultsmentioning
confidence: 99%
“…Along with refugees and minority communities, they are not solely people who have things done to them. Rather, they are proactive in drawing strength from faith communities, creating local and transnational networks, appropriating and adapting available technologies, and affecting conditions at home by sending remittances and exchanging ideas, practices and values (Brees, 2009;Thompson, 2009;Williams, 2008).…”
Section: Talking But Not Dialoguing: the 'Problem' Of Fragmentationmentioning
confidence: 99%